Expressing the will in the electronic contract in light of the Algerian legislation - Aggoni, Mohamed (Journal of Human Sciences, 2022)
I worked through this paper to address a legal approach between commercial contracting via electronic media, the most important of which is the Internet, with the general theory of the contract, in an important part, which is the expression of will in the electronic environment according to Algerian law. The application of the digitization system was reflected in the traditional contractual process as a whole, touching a set of provisions and creating several problems, due to the peculiarity of this type of contract, the most important of which is that it is done through electronic media and is held without the presence of the contracting parties in a real contract council, which created provisions for how to express On the will, the concept, nature and conditions of the electronic offer and acceptance, which differ according to the type of electronic means used, the most important of which are e-mail, web site, chat service or direct viewing.